A Sensible Pragmatist Conception of Truth. (July 2022) - Misak, Cheryl
Abstract: This essay traces the evolution of the pragmatist elements in Wiggins's distinctive view of truth and shows its connections to the founder of pragmatism, C.S. Peirce and one of Peirce's greatest successors, F.P. Ramsey. Wiggin's pragmatism, like that of Peirce and Ramsey, is a pragmatism that attempts to arrive at what Wiggins calls 'a sensible subjectivism' – an account of truth that respects both the human inventiveness and the objectivity that are each a part of our search for the truth